Learning Strategies Used by the Fifth Grade Students in Improving Vocabulary at SDN Kebraon II Surabaya - Alfa Husnul Hakimah; Amrin Batubara; Armeria Wijaya (Tell : Teaching of English Language and Literature Journal, 2014)
This research aims to find out the kinds of strategies and the application of the strategies which are used by the fifth grade students at SDN Kebraon II Surabaya in improving vocabulary. In this research, a qualitative descriptive design is used to describe the objective of the research. The techniques of data collection were used in this research were observation and questionnaire. The data analysis used in this research was the interactive model analysis from Miles and Huberman that consists of data reduction, data display, and conclusion. In the results of this research, it is found that there are twenty one kinds of strategies which are used by the fifth grade students in improving vocabulary. The strategies that were employed by the students mostly were influenced by the teacher's teaching techniques. The orders of the teacher seemingly become a habit for the student to be conducted automatically in the process of language learning.